Spatial characteristics and construction logic of traditional market under land-water transportation influences - Jianqiang Yin; Mengyan Jia; Jingzhao Feng (Humanities & Social Sciences Communications)
Abstract The spatial evolution mechanism of traditional market settlements under the influence of land and water transportation facilities profoundly reflects the dynamic relationship between regional social and economic development and the natural environment. This paper focuses on the market settlement system in the Dongguan region of the Pearl River Delta from 1840 to 1949. By integrating the methods of historical geography, architecture, and anthropology, using GIS spatial analysis, historical map registration, and field investigation, the paper systematically analyzes the spatial characteristics and construction logic of settlements under the influence of land and water complex transportation facilities. The results show that the settlements in Dongguan Market present a heterogeneous spatial distribution pattern, which can be divided into three spatial types: the strip type extending linearly along the water system, the block type dominated by clan power, and the Concave-convex derived from the expansion of the traffic network. On the micro-scale, the spatial organization of streets and lanes forms the topology of the radiation-type, the fish-ridge-type, and the grid-type, revealing the construction wisdom of the synergistic effect of the natural environment, clan governance, and transportation economy. This study provides historical and theoretical support for the protection of traditional settlements. It proposes to build a sustainable path for the coordinated development of the historical environment and modern functions through the linkage development of transportation heritage, the transformation of clan cultural capital, and the application of digital twin technology.